Kinerja Keuangan dan Ukuran Perusahaan terhadap Harga Saham dengan Kebijakan Dividen sebagai Variabel Intervening - Rico Wijaya (University of Merdeka Malang, 2017)
This was research conducted to examine the effect of the leverage ratio, activity ratio, and size firm on stock price with dividend policy as a mediating variable the companies listed in Indonesia Stock Exchange 2012-2014. This research has a total number of samples 141 samples and using purposive sampling with criteria declare a dividend payout for 3 consecutive years, and the debt to equity ratio, total asset turnover, which is positive. The first result is total asset turnover, Ln_totalasset have a positive effect on dividend payout ratio, and debt to equity don’t have a positive effect on the dividend payout ratio. The second result is total asset turnover, Ln_total assets, and dividend payout ratio have a positive effect on Ln_stock prices and debt to equity don’t have a positive effect on Ln_stock prices. Test results mediating dividend payout ratio is not proven mediates the relationship debt to equity, total asset turn over, and Ln_total asset on Ln_stock prices. The result of this research proves that there is no influence of dividend policy in the relation of financial performance to stock price.DOI: https://doi.org/10.26905/jkdp.v21i3.1432